HIV-Related Knowledge and Sexual Behaviors among Teenagers: Implications for Public Health Interventions - Ruyu Liu; Ke Xu; Xingliang Zhang; Feng Cheng; Liangmin Gao; Junfang Xu (MDPI AG, 2023)
Background: Teenagers are at a turning point in people's physical and psychological maturity and are also in a critical period in reproductive and sexual health. It is reported that the initial age at first sexual behavior is younger than decades ago, which implies that the risky sexual behavior among teenagers may be on the rise. However, it is unclear about the changes of sexual knowledge and behaviors in recent years. Methods: Based on the national sentinel surveillance survey in 2011-2021 among students in Hangzhou, we selected out teenagers aged 10-19 years as our study sample. Demographic characteristics (gender, age, marital status, etc.), knowledge of HIV and sexual behaviors were collected. The sexual knowledge score and sexual behaviors were analyzed, and their influencing factors were explored. Results: In total, 1355 teenagers were incorporated in this study; the awareness rates of sexual knowledge in 2011, 2013, 2014 and 2021 were 74.9%, 71.8%, 89.3% and 95.8%, respectively, which showed an overall upward trend. The results of binary logistic regression showed that the survey year, whether students had received and participated in HIV-related publicity services and whether they had sexual behaviors, had a significant influence on whether the awareness rate ≥ 75%. The survey year and whether the awareness rate ≥ 75% had a significant influence on whether students had sexual behaviors. Conclusions: Both the average scores and awareness rates of teenagers' sexual knowledge showed an overall upward trend from 2011 to 2021. Teenagers' initial sexual behavior was at a low age, and the proportion of teenagers who had fixed, temporary and commercial heterosexual sex was still relatively high despite no significant increasing. Therefore, we should further strengthen health education on the risks of sexual behaviors from schools, families and health-related institutions to ensure teenagers receive HIV-related publicity services.